2011
DOI: 10.1287/orsc.1110.0624
|View full text |Cite
|
Sign up to set email alerts
|

The (N)Ever-Changing World: Stability and Change in Organizational Routines

Abstract: This paper uses data on invoice processing in four organizations to distinguish empirically between two competing theories of organizational routines. One theory predicts that routines should generate patterns of action that are few in number and stable over time, and that atypical patterns of action are driven primarily by exceptional inputs. The competing theory predicts the opposite. By modeling the routines as networks of action and using a first-order Markov model to test for stationarity, we find support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 48 publications
3
135
0
8
Order By: Relevance
“…To the extent that the identified dynamic change of behaviors are equivalent or similar to organizational routines, we argue that our findings are in line with Feldman (2000), Pentland and Feldman (2005) and Pentland, Haerem and Hillison's (2011) research on the dynamic nature of organizational routines, since the influenced behaviors are not only verified and changed through nuanced actions; they are also developed to induce future changes via proactive exploration and search for new insight. Here research on organization design and its necessary fit with organization routines cf.…”
Section: Discussionsupporting
confidence: 79%
“…To the extent that the identified dynamic change of behaviors are equivalent or similar to organizational routines, we argue that our findings are in line with Feldman (2000), Pentland and Feldman (2005) and Pentland, Haerem and Hillison's (2011) research on the dynamic nature of organizational routines, since the influenced behaviors are not only verified and changed through nuanced actions; they are also developed to induce future changes via proactive exploration and search for new insight. Here research on organization design and its necessary fit with organization routines cf.…”
Section: Discussionsupporting
confidence: 79%
“…A good example of such research is found in Pentland et al (2011) in their use of data on invoice processing in four different organizations with a view to examining organizational routines. Their finding that there were many unique patterns generated by these routines, rather than just a few stable patterns, is illustrative of the emergence of which we have spoken, and of the more nuanced accounts that we seek.…”
Section: Future Directions In Methodologymentioning
confidence: 99%
“…Researchers would thus 'complicate' their research approach. An example would be analytics research that 'mines' business processes ( Van der Aalst, 2012;Pentland et al, 2011), but can also be used for revealing patterns in qualitative data (Schreier, 2015). The resulting two types of stories can be related relying on a dialectical or sequential (Lee, 1991) approach.…”
Section: Implications For Researchmentioning
confidence: 99%